(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The main goal of the paper is to analyse the objectives declared by the twenty professional associations of public relations, from the perspective of ethics. To answer in which way PR-associations consider ethics as one of the objectives of their work, the research used the qualitative content analysis of the official web-sites of twenty different professional (inter)national associations in Europe and US. The research showed that the majority of the associations emphasized the ethical dimension of their efforts, although it is not unanimously shared, since some of them express it in a very vague way. Nevertheless, the majority of analysed professional associations are aware of the importance of ethics in public relations and of their own strategical role in the field of public relations ethics. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.